Case Report: Diagnostic challenges in differentiated-type vulvar intraepithelial neoplasia - Peng, Jifeng; Li, Yanyan; Sun, Xiaoling; Hu, Jianxin; Bai, Ying; Yang, Hui; Wang, Yan; Gao, Xiaolong; Yin, Peihao; Dong, Yuling (Frontiers in Oncology, 2025)
Differentiated-type vulvar intraepithelial neoplasia (dVIN) is typically HPV-independent and is most strongly linked to HPV-independent keratinizing squamous cell carcinoma (often well- to moderately differentiated). It commonly shows aberrant p53 and p16-negative immunophenotype. As such, dVIN carries a higher risk of progression to invasion and metastasis, tends to progress to carcinoma more rapidly, and predominantly affects older women. In this study, we report two cases of vulvar squamous cell carcinoma (VSCC) associated with dVIN, aiming to enhance awareness of its pathological and clinical features. In both cases, the patients tested negative for human papillomavirus (HPV), and the tumors presented as well-differentiated, keratinizing squamous cell carcinoma (keratinizing SCC) with lymph node metastasis. In Case 1, the initial pathological diagnosis was misinterpreted as inflammation or mild-to-moderate epithelial hyperplasia. It was only upon lymph node metastasis and further immunohistochemical review (including mutant-type p53, negative p16, and positive CK17 and SOX2) that dVIN was confirmed, suggesting a possible early microinvasive lesion that had been overlooked. In Case 2, the ulcerated, bleeding lesion was diagnosed as SCC with adjacent areas of dVIN, supported by immunohistochemical findings. These two cases highlight that although dVIN may appear histologically subtle, it can directly progress to SCC and even metastasize when overt invasion is not appreciated on the index biopsy. It may be prudent to maintain increased vigilance for persistent vulvar lesions, particularly in HPV-negative and histologically ambiguous settings. Comprehensive assessment (including immunohistochemistry) may facilitate earlier detection and more accurate diagnosis, thereby potentially improving treatment outcomes.